Brief Report: Rates of Fentanyl Use Among Psychiatric Emergency Room Patients. Issue 1 (10th August 2020) - Elmarasi, Mohamed; Garcia‐Vassallo, Gabriela; Campbell, Sheldon; Fuehrlein, Brian
Abstract : Background and Objectives: Opioid overdose‐related deaths increased from approximately 18 000 deaths in 2007 to 46 802 deaths in 2018. Fentanyl is primarily responsible for the increase in opioid overdose deaths from 2011 through 2017. The primary aim of this study is to determine the rates of fentanyl in the urine drug screens of all patients who presented to the psychiatric emergency room at VA Connecticut, over 7 months in 2018. Methods: Data were collected for all patient presentations between June 2018 and December 2018. There were 746 total patient presentations, with 497 being unique. Collected data included basic demographic information, psychiatric diagnosis, and urine drug screen for various illicit substances, including fentanyl. Results: Over 15% of patients screened positive for fentanyl. Patients who tested positive for fentanyl were further classified based on positive urine drug screening results for other opioids, cocaine, or both. Twenty percent of patients who screened positive for fentanyl and cocaine tested negative for other opioids. This category suggests that some veterans might be consuming fentanyl with cocaine. Discussion and Conclusions: Fentanyl was found at a high rate, even in the absence of other opioids, which suggests that some veterans might be consuming fentanyl with cocaine. Consequently, harm reduction strategies should be broadened to include all patients at risk of fentanyl overdose, including patients who use substances (eg, cocaine) that are potentially adulterated with fentanyl. Scientific Significance: This study is the first one of its kind that looked at rates of fentanyl use in all presentations to a psychiatric emergency room. While it is well‐known that fentanyl is highly prevalent, these findings extend the current state of knowledge by replication in a psychiatric emergency population. (Am J Addict 2021;30:92–95)